2019
DOI: 10.1155/2019/8746895
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor p53 Suppresses Tumor Growth by Prompting Pyroptosis in Non-Small-Cell Lung Cancer

Abstract: Objective To evaluate the effect of p53 on pyroptosis and its inhibitory role on tumor growth in non-small-cell lung cancer (NSCLC). Methods The correlation of p53 and pyroptosis was determined in tumor tissues of NSCLC patients. The pyroptotic level was detected in A549 cells to clarify the effect of p53 on pyroptosis. p53 overexpression A549 tumor-bearing mice were used to clarify the therapeutic target of p53 in NSCLC treatment. Results p53 expression level was positively related to pyroptosis in NSCLC tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 32 publications
2
67
0
Order By: Relevance
“…Transcription factor p53 overexpression triggers pyroptosis to suppress tumor growth in A549 tumor-bearing mice. In clinical trials, p53 expression level is positively related to pyroptosis in tumor tissue of NSCLC patients, implicating the potentiality of p53 on antitumor via induction of pyroptosis [20]. The studies provide new ideas to support pyroptosis as a novel mechanism of molecular-targeted drugs to exterminate oncogene-addicted tumor cells.…”
Section: Non-chemotherapy Drug-induced Pyroptosis Exerts Anticancer Ementioning
confidence: 86%
See 1 more Smart Citation
“…Transcription factor p53 overexpression triggers pyroptosis to suppress tumor growth in A549 tumor-bearing mice. In clinical trials, p53 expression level is positively related to pyroptosis in tumor tissue of NSCLC patients, implicating the potentiality of p53 on antitumor via induction of pyroptosis [20]. The studies provide new ideas to support pyroptosis as a novel mechanism of molecular-targeted drugs to exterminate oncogene-addicted tumor cells.…”
Section: Non-chemotherapy Drug-induced Pyroptosis Exerts Anticancer Ementioning
confidence: 86%
“…On the other hand, resisting cell death is the important hallmark of cancers [19]. Induction of cancer cell pyroptosis by various stimulations can eliminate malignant cells [20][21][22][23][24]. Although pyroptotic death is often harmful to normal tissues, it can be beneficial to cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, P53 was significantly upregulated in LPS-induced A549 pyroptosis. In conclusion, P53 might promote pyroptosis via binding and activating NLRP3 directly (59). Noncoding RNA also participates in the canonical pyroptosis of NSCLC.…”
Section: Lung Cancermentioning
confidence: 89%
“…TP53 is a well-known tumor suppressor that induces growth arrest or apoptosis and involved in cell cycle regulation. 28 TP53 is downregulated in many types of tumors including non-small cell lung cancer, colorectal cancer, cervical cancer and ovarian cancer, [29][30][31][32][33][34] which can lead to a poor survival rate. Our results showed that TP53 was downregulated in OC tissues, and could be decreased by miR-183-5p mimics and restored by overexpressed LEMD1-AS1, respectively.…”
Section: Discussionmentioning
confidence: 99%